Physical development and eating habits of a group of teenagers from Dimitrie Cantemir high school in Iasi - ALBU, Adriana; ABDULAN, Irina; GHICA, Catalin Dragos (One Health & Risk Management, 2021)
Introduction. Eating habits are formed in the first years of life and sometimes persist throughout life. It is necessary to develop coherent nutritional educational programs to guide adolescents towards a healthy diet. It is an essential aspect in the current conditions when the identification with the ideal of beauty is essential, especially for girls. Also, great attention is needed because in Romania, especially in the area of Moldova, there is a strong anchoring in traditions, so that eating habits are difficult to change. Material and methods. The study was conducted on a group of 194 students from the ninth grade (112 young people) and the twelfth grade (82 students) from Dimitrie Cantemir High School in Iasi. The study group consists of 126 girls (64.94%) and 68 boys (35.05%). These young people were appreciated for their physical development with the help of body mass index and eating habits. Eating habits were assessed on the basis of a weekly food intake questionnaire. The consumption of milk, chicken, meat dishes, vegetables and sugar/sweets was appreciated. The response variants are: zero, once a week, 2-3 times a week, 4-6 times a week and daily. The processing of the results was done on the classes and according to the sex of the students with the help of the Pearson test. Results. Physical development falls mainly at normal values (68.55%). There are 19.07% underweight students but also 12.37% young people with obesity. The calculated differences are statistically insignificant by class, but significant (p˂0.01) depending on the sex of the students. Attention is drawn to girls whose percentage of malnutrition is high. Milk is present in menus especially 2-3 times (35.05%) or 1 time (25.77%) per week, with insignificant differences by class and sex. Chicken meat is consumed mainly 2-3 times a week (42.78%) with insignificant differences by classes, but significant by sex (p˂0.001). Girls have a high consumption of chicken meat that provides few calories per 100 g of product. Meat dishes are present in the students’ diet, especially 2-3 times (31.95%) or once (27.31%) per week. There is a high percentage of girls who mark the zero variant, the calculated differences being statistically significant (p˂0.05) depending on the sex of the young people, but statistically insignificant by classes. Vegetables are consumed especially 2-3 times (30.92%) per week or daily (28.35%), the calculated differences being statistically insignificant. Sugar/sweets are consumed mainly daily (29.89%) or 2-3 times (26.28%) per week. The calculated differences are statistically significant (p˂0.05) and draw attention to girls who have an increased percentage of daily responses, but insignificant by classes. Conclusions. The eating habits of students surveyed differently in girls than in boys, an aspect that draws attention to young females for whom identification with the current ideal of beauty is essential.